2008
DOI: 10.1523/jneurosci.4771-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Oligomers (Aβ1–42Globulomer) Suppress Spontaneous Synaptic Activity by Inhibition of P/Q-Type Calcium Currents

Abstract: Abnormal accumulation of soluble oligomers of amyloid ␤ (A␤) is believed to cause malfunctioning of neurons in Alzheimer's disease. It has been shown that A␤ oligomers impair synaptic plasticity, thereby altering the ability of the neuron to store information. We examined the underlying cellular mechanism of A␤ oligomer-induced synaptic modifications by using a recently described stable oligomeric A␤ preparation called "A␤ 1-42 globulomer." Synthetically prepared A␤ 1-42 globulomer has been shown to localize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(176 citation statements)
references
References 30 publications
9
160
2
Order By: Relevance
“…Aβ was also shown to inhibit presynaptic P/Q Ca 2+ channels, suppressing spontaneous synaptic activity (Mezler et al, 2012;Nimmrich et al, 2008), along with the activation of presynaptic α7-nicotinic acetylcholine (ACh) receptors (Dougherty et al, 2003). More recently, Aβ was reported to directly modulate recombinant P/Q-type and also N-type Ca 2+ channels in HEK293 cells and blockade of presynaptic Ca 2+ channels reversed…”
Section: Aβ At Presynaptic Level and Glial Cellsmentioning
confidence: 99%
“…Aβ was also shown to inhibit presynaptic P/Q Ca 2+ channels, suppressing spontaneous synaptic activity (Mezler et al, 2012;Nimmrich et al, 2008), along with the activation of presynaptic α7-nicotinic acetylcholine (ACh) receptors (Dougherty et al, 2003). More recently, Aβ was reported to directly modulate recombinant P/Q-type and also N-type Ca 2+ channels in HEK293 cells and blockade of presynaptic Ca 2+ channels reversed…”
Section: Aβ At Presynaptic Level and Glial Cellsmentioning
confidence: 99%
“…Finally, the improved spine density and cognitive function in APP transgenic mice after A-887755 treatment raises the hope that selective A␤ oligomer immunotherapy is a promising therapeutic approach without side effects associated with general anti-A␤ therapy. In addition, the globulomer concept will assist in reaching a clearer understanding of the molecular mechanisms of A␤ oligomer pathology, like a recently described interference with the presynaptic P/Q-type calcium current (Nimmrich et al, 2008).…”
mentioning
confidence: 99%
“…Many studies have reported the roles of VGCCs in CNS injuries and diseases. For instance, N-type VGCC is a key component in controlling the transmission of nociceptive signals (Altier et al 2006), and the inhibition of P/Q-type VGCCs mediates the suppression of spontaneous synaptic activity by amyloid b oligomers (Nimmrich et al 2008). In addition, the entry of L-type VGCCs has been associated with neuronal death in Alzheimer's disease (Yagami et al 2004), ischemia (Li et al 2007), and glutamate toxicity (Sribnick et al 2009).…”
Section: Camentioning
confidence: 99%